Der "Deutsche Gruß" in Briefen. Zur historischen Soziolinguistik und Pragmatik eines verordneten Sprachgebrauchs - Ehlers, Klaas-Hinrich (Linguistik Online, 2012)
The official decree, in 1933, to use "Heil Hitler" and "Mit deutschem Gruß [With German greetings]" as greetings, constituted a massive intervention in the everyday use of language in the German population. The study examines in what time frame and in what domains of written communication the new forms of greeting were established. Sources include guidelines and sample letters from Nazi era style guides as well as a body of authentic business letters from the 1920s to 1940s. The development described in the study is characterized as a phase of forcibly accelerated modernization in the long-term history of European communication routines. The introduction of the Hitler salute is identified as a premature and passing episode in the multidimensional transition from feudal courtesy of the vertical distance towards a bourgeois/contemporary courtesy of the horizontal distance.